GAMBARAN PENGETAHUAN SISWA KELAS VII TENTANG POLA SIKLUS MENSTRUASI DI SMP NEGERI 2 DOLOK PARDAMEAN KABUPATEN SIMALUNGUN TAHUN 2022 - Meriati Bunga Arta Purba; Dearni Sulastri Malau (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2022)
Background : Menstruation can be defined as regular bleeding from the uterus as a sign that the uterine organs are functioning properly or are ready to reproduce. Generally, teenagers who experience their first menstruation (menarche) are at the age of 12 to 16 years. A normal menstrual cycle will occur every 22-35 days with a menstrual period of approximately 2-7 days. Menstruation can be troublesome for girls, this is generally due to lack of or incorrect information about menstruation. Generally people are afraid to see blood, especially children. His ignorance can lead to it mistakenly, linking menstruation to illness or injury and even viewing it as something shameful, for not getting a proper explanation. Objective : To describe the knowledge of seventh grade students about menstrual cycle patterns in adolescents at SMP Negeri 2 dolok pardamean Research method : The design of this study user a quantitative descriptive method, with a Cross Sectional research design using a population of 45 and a sample of 45 samples, with a sampling technique. by Aqidental sampling, and in collecting data using a questionnaire with univariate analysis, frequency and percent. The conclusion is based on the results of the study with a sample of 45 respondents regarding the description of the knowledge of class VII students about the menstrual cycle pattern at SMP Negeri 2 Dolok Pardamean Simalungun Regency. Suggestion to learn all about the menstrual cycle pattern in schools at SMP Negeri 2 Dolok Pardamean, Simalungun Regency. It is hoped that there will be material about menstruation in learning outcomes in order to access some about menstruation both through books and social media.